INCREASING STUDENTS SELF-REGULATED LEARNING THROUGH A REALISTIC MATHEMATICAL EDUCATION - Rama Nida Siregar; Didi Suryadi; Sufyani Prabawanto; Abdul Mujib (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
This research is motivated by the importance of students' self-regulated learning. Aims to determine the increase in self-regulated learning of students with a realistic mathematical education in learning mathematics and to know student responses. This type of research is descriptive research through questionnaire analysis. The instruments used were a self-regulated learning questionnaire and a questionnaire to see student responses. In this study, the data obtained were analyzed using a Likert attitude scale. This scale in self-regulated learning contains nine components, namely: assessing students for (1) learning initiatives, (2) diagnosing learning needs, (3) setting learning goals, (4) monitoring, organizing and controlling learning, (5 seeing difficulties as a challenge, (6) utilizing and searching for relevant learning resources, (7) selecting and determining learning strategies, (8) evaluating learning processes and outcomes, and (9) self-concept. The conclusions obtained in this study are related to self-regulated learning in mathematics can be seen as a whole by using realistic mathematics education. This shows that there are 96.76% of students who give a positive response.